2017
DOI: 10.1002/brb3.761
|View full text |Cite
|
Sign up to set email alerts
|

Vitamin D supplementation differentially affects seasonal multiple sclerosis disease activity

Abstract: Objectives: Low ultraviolet-B (UVB) radiation causes hypovitaminosis D, which is a known risk factor for multiple sclerosis (MS) and associated with MS disease activity.Our objective is to test whether vitamin D supplementation is most effective in lowering disease activity during the period of the year with low UVB radiation and conse-

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
16
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
9
1

Relationship

2
8

Authors

Journals

citations
Cited by 24 publications
(17 citation statements)
references
References 25 publications
0
16
1
Order By: Relevance
“…Surprisingly, we found no consistent evidence of an association between post-FDE sun exposure and either MS conversion or relapse hazard, nor between postonset serum 25(OH)D levels and clinical course. These null findings were unexpected and inconsistent with other observations in support of a role for vitamin D in MS clinical course ( 20 24 , 26 , 27 , 51 53 ). It raises the question whether there truly is no association (affirming the null hypothesis) or whether the study failed to detect an association (a false negative).…”
Section: Discussioncontrasting
confidence: 99%
“…Surprisingly, we found no consistent evidence of an association between post-FDE sun exposure and either MS conversion or relapse hazard, nor between postonset serum 25(OH)D levels and clinical course. These null findings were unexpected and inconsistent with other observations in support of a role for vitamin D in MS clinical course ( 20 24 , 26 , 27 , 51 53 ). It raises the question whether there truly is no association (affirming the null hypothesis) or whether the study failed to detect an association (a false negative).…”
Section: Discussioncontrasting
confidence: 99%
“…We collected data of patients treated at European MS centers located in Athens (Greece), Bern (Switzerland), Bochum (Germany), and Peine (Germany). In the participating centers, data were gathered from medical records and from previously published retrospective MS studies with different nonepidemiological scopes . The study was approved by the responsible local ethics committees (Eginition Hospital, Athens University Medical School; Bern University Hospital: KEK‐BE 2017‐01369; Ruhr‐University Bochum: 5408‐15; Medical Association of Lower Saxony (06/17/16)).…”
Section: Methodsmentioning
confidence: 99%
“…Since in both studies, SOLAR and CHOLINE, cholecalciferol was used as an add-on to interferon-beta, it is important to mention that in patients being treated with interferon-beta who received repeated MRI scans and measurements of serum 25(OH)D concentration, an inverse correlation between 25(OH)D and MRI activity was found before but not during treatment with interferon-beta (126). Other vitamin D supplementation studies investigating relapse risk, CNS lesions, and/or disability progression were either substantially smaller, or of shorter duration, or were not prospectively randomized and are therefore only listed in the reference section [see (127)(128)(129)(130)]. Regarding the effects of vitamin D supplementation on fatigue and depression scores, Rolf et al showed in a prospectively studied cohort of 40 MS patients that patients receiving cholecalciferol for 48 weeks did not improve significantly in fatigue or depression scores in comparison to placebo (131).…”
Section: Vitamin D Supplementation and Its Association With Ms Risk Amentioning
confidence: 99%